2020
DOI: 10.1186/s12884-020-02943-7
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric pain correlates with postpartum depression symptoms: a pilot prospective observational study

Abstract: Background: Data linking labor pain and postpartum depression are emerging. Robust, prospective evaluations of this relationship while factoring other important variables are lacking. We assessed perinatal pain and other factors predicting postpartum depression (PPD) symptoms. Methods: Third trimester women, stratified by a priori plan to receive or avoid labor epidural analgesia, were longitudinally followed from the prenatal period through labor and delivery, until 6 weeks and 3 months postpartum. Electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 44 publications
(57 reference statements)
2
53
0
1
Order By: Relevance
“…The present study identifies a relationship between this noncoding RNA SNP (rs11135349) and labor pain unpleasantness; our own data have similarly found that labor pain unpleasantness is significantly associated with depression scores at six weeks postpartum, in women planning/receiving labor epidural analgesia (R 2 ¼ 0.41; P ¼ 0.001). 55 Together, these findings suggest that this noncoding RNA species may contribute to disease etiology not only for depression phenotypes but also for labor pain.…”
Section: Discussionmentioning
confidence: 88%
“…The present study identifies a relationship between this noncoding RNA SNP (rs11135349) and labor pain unpleasantness; our own data have similarly found that labor pain unpleasantness is significantly associated with depression scores at six weeks postpartum, in women planning/receiving labor epidural analgesia (R 2 ¼ 0.41; P ¼ 0.001). 55 Together, these findings suggest that this noncoding RNA species may contribute to disease etiology not only for depression phenotypes but also for labor pain.…”
Section: Discussionmentioning
confidence: 88%
“…More recently, Lim et al revealed perinatal pain during multiple time points including prenatal, intrapartum, and postpartum independently predicts six-week EPDS scores. 16 Eisenach et al demonstrated that acute postpartum pain severity predicted a 3-fold increased risk for PPD at 8 weeks. 5 A large Canadian cohort of 5,614 women assessed for PPD using a cut-off score of 13 on the EPDS (Edinburgh Postnatal Depression Scale) found an increased risk of PPD at 3 months in women reporting prolonged perinatal pain.…”
Section: Results/data Analysismentioning
confidence: 99%
“…However, whether the pain syndrome is of neuropathic nature is unknown. 27 The SF-MPQ-2 was used in Cesarean delivery to evaluate for post-delivery chronic neuropathic pain; however, there is limited information on its use in those undergoing labor process. 28 We demonstrated that pre-delivery neuropathic pain, as measured by SF-MPQ-2, was associated with postnatal anxiety and/or depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…25 During labor, neuropathic pain may arise from direct pressure on the lumbosacral plexus, which is left exposed to the pelvic area, and the pain may usually be resolved after the childbirth process. 25 Previous studies have suggested an association between the intensity of labor pain and PND development; 26,27 a prospective observational study in 72 women showed that increased pain at each perinatal time point (pre-delivery, labor, postdelivery) was independently associated with increased EPDS scores at 6 weeks after delivery. However, whether the pain syndrome is of neuropathic nature is unknown.…”
Section: Discussionmentioning
confidence: 99%